Diacylglycerol Kinase ζ Attenuates Doxorubicin‐Induced Cardiotoxicity Through p53 Degradation - Shingo Tachibana; Yoichiro Otaki; Tetsu Watanabe; Jun Goto; Haruki Ochi; Toshiaki Tanaka; Hiroe Ono; Ryuhei Yamaguchi; Junya Sato; Hiroki Takahashi; Takanori Arimoto; Kaoru Goto; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Doxorubicin‐induced cardiotoxicity is still an important medical problem associated with a high mortality rate in cancer survivors. p53 plays a key role in doxorubicin‐induced cardiotoxicity. Diacylglycerol kinase ζ (Dgkζ), a 130‐kDa enzyme abundant in cardiomyocytes, regulates the p53 protein expression level in neurons. To elucidate the mechanism of doxorubicin‐induced cardiotoxicity, we focused on the functional role of Dgkζ and its interaction with heat shock protein 70 (Hsp70)–related ubiquitin E3 ligases such as E6‐associated protein (E6ap) and C‐terminus of Hsp70‐interacting protein. Methods and Results Protein interactions of Dgkζ with Hsp70 and E6ap were confirmed by immunoprecipitation, but not C‐terminus of Hsp70‐interacting protein. We administered doxorubicin in cardiac‐specific overexpression of Dgkζ transgenic (Dgkζ‐Tg) mice and wild‐type littermates. Dgkζ‐Tg mice showed lower p53 protein expression levels, preserved cardiac function, and improved survival rates compared with wild‐type littermates after doxorubicin administration. RNA sequence analysis of myocardial tissues from Dgkζ‐Tg after doxorubicin stimulation identified Hspa1b encoding Hsp70 as the differentially expressed gene. Dgkζ overexpression increased proteasomal p53 degradation and attenuated cardiomyocyte apoptosis after doxorubicin stimulation in cardiomyocytes, which was reversed by knockdown of E6ap. Dgkζ interacted with E6ap through ankyrin‐like repeats. The overexpression of mutant Dgkζ, lacking ankyrin‐like repeats, failed to inhibit p53 protein expression after doxorubicin stimulation. In Dgkζ‐overexpressing cardiomyocytes, expression levels of p53 and caspase‐3 were increased by knockdown of the C‐terminus of Hsp70‐interacting protein. Conclusions We demonstrated for the first time that Dgkζ augments p53 ubiquitin‐proteasome degradation and ameliorates doxorubicin‐induced cardiotoxicity by interacting with Hsp70 and E3 ligases such as E6ap and C‐terminus of Hsp70‐interacting protein.